Perlindungan Konsumen Dalam Perjanjian Jual Beli Online - Maatuil, Rexy Andalangi; Olfina Manatar; Jesica kiara Agumanis; Abbelia Ardiva Bawanda; Zulkifli Liputo; Marchello Rori (Indo Publishing, 2025)
The development of e-commerce provides convenience for consumers, but also raises various legal issues, especially in online sales agreements. This study aims to analyze the form of consumer protection and determine the extent to which existing regulations are able to provide legal certainty for the parties. The method used is a literature study through a review of books, journals, and laws and regulations relevant to electronic transactions and consumer protection. The results of the study indicate that non-conformity of goods, incomplete product information, and lack of responsibility of business actors remain the main problems experienced by consumers. Although regulations such as the Consumer Protection Law, the ITE Law, and Government Regulation No. 80 of 2019 have provided a legal basis, the effectiveness of their implementation still depends on business actor compliance and consumer literacy levels. This study emphasizes the importance of strengthening education, information transparency, and more intensive supervision to create safe and balanced online transactions for consumers. Consumer protection has been regulated in Law Number 8 of 1999 and regulations related to electronic transactions, but its implementation still faces various obstacles, such as unclear information, seller identity verification, and the effectiveness of complaint channel.